Tea Party bevægelsen:: Almindelig sund fornuft - Nielsen, Paul Gammelbo (Slagmark - Tidsskrift for idéhistorie, 2018)
The article uses the 2010 political success of the Tea Party phenomenon as a jumping-off point to examine a number of ideological tropes and rhetorical devices in American politics. It argues that the political language of the Tea Party is not – as is often assumed – empty moralizing at the expense of intellectual depth, but rather draws on a wide variety of American political and intellectual themes and traditions. The article uses the campaign literature and polemic of key Tea Party affiliates – Sarah Palin, Christine O’Donnell, Glenn Beck, Ron Paul – as entry points to discuss the movement’s political strategies and interpretation of the role of government, individual liberty, American exceptionalism, constitutionalism, the free market, and the common people. In placing these discussions in their historical and intellectual context, the article argues for taking the Tea Party’s political message seriously, not least as a reflection of prevalent democratic concerns and frustrations with the American political system in its current incarnation.